Bempedoic Acid Lowers Low-Density Lipoprotein Cholesterol and Attenuates Atherosclerosis in Low-Density Lipoprotein Receptor–Deficient (LDLR+/− and LDLR−/−) Yucatan Miniature Pigs. Issue 5 (May 2018) - Burke, Amy C.; Telford, Dawn E.; Sutherland, Brian G.; Edwards, Jane Y.; Sawyez, Cynthia G.; Barrett, P. Hugh R.; Newton, Roger S.; Pickering, J. Geoffrey; Huff, Murray W.
Abstract : Objective—: Bempedoic acid (BemA; ETC-1002) is a novel drug that targets hepatic ATP-citrate lyase to reduce cholesterol biosynthesis. In phase 2 studies, BemA lowers elevated low-density lipoprotein cholesterol (LDL-C) in hypercholesterolemic patients. In the present study, we tested the ability of BemA to decrease plasma cholesterol and LDL-C and attenuate atherosclerosis in a large animal model of familial hypercholesterolemia. Approach and Results—: Gene targeting has been used to generate Yucatan miniature pigs heterozygous ( LDLR +/− ) or homozygous ( LDLR −/− ) for LDL receptor deficiency (ExeGen). LDLR +/− and LDLR −/− pigs were fed a high-fat, cholesterol-containing diet (34% kcal fat; 0.2% cholesterol) and orally administered placebo or BemA for 160 days. In LDLR +/− pigs, compared with placebo, BemA decreased plasma cholesterol and LDL-C up to 40% and 61%, respectively. In LDLR −/− pigs, in which plasma cholesterol and LDL-C were 5-fold higher than in LDLR +/− pigs, BemA decreased plasma cholesterol and LDL-C up to 27% and 29%, respectively. Plasma levels of triglycerides and high-density lipoprotein cholesterol, fasting glucose and insulin, and liver lipids were unaffected by treatment in either genotype. In the aorta of LDLR +/− pigs, BemA robustly attenuated en face raised lesion area (−58%) and left anterior descending coronary artery cross-sectional lesion area (−40%). In LDLR −/− pigs, in which lesions were substantially more advanced, BemA decreased aortic lesion area (−47%) and left anterior descending coronary artery lesion area (−48%). Conclusions—: In a large animal model of LDLR deficiency and atherosclerosis, long-term treatment with BemA reduces LDL-C and attenuates the development of aortic and coronary atherosclerosis in both LDLR +/− and LDLR −/− miniature pigs. Abstract : Supplemental Digital Content is available in the text.